Relevance and Flexibility of the Mufassir’s Requirements: A Critical Study of the Principle Kullu Man Fassara Al-Qur’an Fa ‘Alaihi Bi ‘Ilm At-Tafsīr: Relevansi dan Fleksibilitas Syarat Mufassir: Telaah Kritis Qa’idah Kullu Man Fassara Al-Qur’an Fa ‘Alaihi Bi ‘Ilm At-Tafsīr - Haikal, M Arsyad (SiRad: Pelita Wawasan, 2025)
The principle (kaidah) kullu man fassara Al-Qur’an fa ‘alaihi bi ‘ilm at-tafsīr (Whoever interprets the Qur'an must do so with the knowledge of tafsir) is one of the fundamental principles in the discipline of tafsir (Qur'anic exegesis). This principle asserts that anyone who interprets the Qur'an must do so with the knowledge of tafsir, not based on personal desires (hawa nafsu), assumptions, or mere conjecture. However, in contemporary reality, this principle is often understood narrowly, both by those who disregard it completely and by those who adhere to it rigidly and ahistorically. This paper seeks to examine the meaning, basis (dalil), and practice of this principle in the history of tafsir and in the contemporary Indonesian context. Using a qualitative approach and the Socratic dialectical analysis method, this paper finds that the requirements for a mufassir (interpreter) both mental-spiritual and intellectual are partly universal and partly temporal and contextual. Therefore, the approach to this principle must be critical and inclusive, so that the interpretation of the Qur'an remains alive and able to respond to the challenges of the times. This research also highlights that the flexibility in the requirements for a mufassir does not mean denigrating the science of tafsir, but rather opens space for the development of an interpretation that is both academically responsible and socially relevant. (Kaidah kullu man fassara Al-Qur’an fa ‘alaihi bi ‘ilm at-tafsīr merupakan salah satu prinsip fundamental dalam disiplin tafsir. Kaidah ini menegaskan bahwa siapa pun yang menafsirkan Al-Qur’an harus melakukannya dengan ilmu tafsir, bukan dengan hawa nafsu, asumsi, atau dugaan semata. Namun, dalam realitas kontemporer, kaidah ini sering dipahami secara sempit, baik oleh kalangan yang mengabaikannya secara total, maupun oleh mereka yang memegangnya secara kaku dan ahistoris. Tulisan ini berusaha mengkaji makna, dalil, serta praktik kaidah tersebut dalam sejarah tafsir dan dalam konteks keindonesiaan masa kini. Dengan menggunakan pendekatan kualitatif dan metode analisis dialektika Socrates, tulisan ini menemukan bahwa syarat-syarat bagi seorang mufassir baik mental-spiritual maupun intelektual sebagian bersifat universal dan sebagian lainnya bersifat temporal dan kontekstual. Oleh karena itu, pendekatan terhadap kaidah ini harus bersifat kritis dan inklusif, agar tafsir Al-Qur’an tetap hidup dan mampu menjawab tantangan zaman. Penelitian ini juga menyoroti bahwa fleksibilitas syarat mufassir bukan berarti merendahkan ilmu tafsir, melainkan membuka ruang bagi pengembangan tafsir yang bertanggung jawab secara keilmuan sekaligus relevan secara sosial.)